Key Performance Metrics for Green Warehousing in Manufacturing Supply Chains: A Review - Meliana, Dita; Hasibuan, Sawarni (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
This research highlights the significance of adopting eco-friendly methods in storage, which is a vital part of the manufacturing supply chain. Although green warehousing is still in its early stages, and there is less literature and empirical data on the subject, its potential for sustainable growth is enormous and requires additional exploration. The study's objective is to identify areas in research that have not been adequately addressed and to establish key performance indicators (KPIs) relevant to green warehousing. This will be achieved by a thorough invesstigation of existing literature. The research methodology employs well-regarded databases such as Publish or Perish, Proquest, and Google Scholar. It utilizes keywords such as